MODEL KEPEMIMPINAN STRATEGIK BERBASIS INTEGRITAS DAN PANCASILA DALAM PENGELOLAAN SDM PERTAHANAN ADAPTIF MENUJU INDONESIA EMAS 2045 - Muhammad Hadis Hamsyah; Anto Indriyanto; Tarsisius Susilo; Budiman Marpaung; Bambang Budi Kuncoro (Berajah Journal, 2025)
This study discusses the urgency of an integrity-based strategic leadership model and Pancasila in adaptive defence human resource management towards Indonesia Emas 2045. The aim is to formulate a conceptual framework capable of responding to the complexity of global challenges characterised by an era of volatility, uncertainty, complexity, and ambiguity. The research uses qualitative methods with a systematic literature review approach to relevant national and international literature for the period 2000–2025. The results of the study show that effective strategic leadership requires the integration of three main pillars: national values based on Pancasila, the internalisation of integrity as a moral foundation, and adaptive resilience capacity in the face of hybrid threats. The discussion emphasises that these three pillars interact with each other to form an integrative leadership model that can strengthen the character, professionalism, and competitiveness of defence human resources while ensuring moral legitimacy and national cohesion. These findings have implications for the formulation of defence policies that emphasise a balance between technical competence, national values, and strategic adaptability. Thus, this study contributes to enriching the literature on strategic leadership and offers practical guidance for the development of Indonesian defence human resources that are characterful, sustainable, and visionary.